The level of zakat recipient satisfaction towards management of zakat: A study in MAIWP / Nur Nadhirah Mohd Hanafi - Mohd Hanafi, Nur Nadhirah (Academy of Contemporary Islamic Studies, 2018)
The issue of zakat distribution is often a concern. The fact arises the issue of zakat management effectiveness as performed by the 13 Malaysian State Islamic Religious Councils. Thus, this study examines the level of satisfaction among the zakat recipients towards the management of zakat in the State Islamic Religious Council of Wilayah Persekutuan (Majlis Agama Islam Wilayah Persekutuan abbreviated as MAIWP). For that purpose, a set of questionnaire had been distributed to zakat recipients in Wilayah Persekutuan. The questionnaires consist of four sections; Section A contains selected demographic variables, Section B measures the satisfaction towards the source of information, Section C measures satisfaction towards the customer services, while Section D measures satisfaction towards the procedure of zakat as executed by MAIWP. The data collected through the questionnaires were analyzed using Statistical Packages for Social Sciences (SPSS) software 20.0.